An unusual presentation of epidermoid cyst in an adult male in India: A case report - Singh, Hershdeep; Dua, Sanjeev; Dhar, Anil; Goel, Amitabh (Eastern Journal of Medical Sciences, 2023)
The epidermoid cysts are true cysts that are often found in the face and less commonly in the trunk and back of the human body. These cysts often have a predilection toward the male gender with the third and fourth decades of age group. They generally arise from the follicular infundibulum, primarily due to plugging of the follicle. Often a part of genetic syndromes, they can also be post-traumatic where the ectodermal cells get stuck or reimplanted. Epidermoid cysts are often a slow-growing and painless lesion with few exceptions. The proper neurological examination, clinical examination, and investigations such as magnetic resonance imaging help in confirming the diagnosis and proceeding with the management. Clinically, epidermoid cysts may or may not present with the neurological impairment. The preferred intervention is total or subtotal resection with minimal chances of complications such as recurrence, swelling, and infection. However, these can very well be avoided by regular follow-up assessments. The clinical presentation in the lower back with massive dimensions is relatively uncommon, and therefore, authors have presented here an unusual case from the outpatient department of neurosurgery, where the patient presented with a large, soft, exophytic lesion at the level of (S4/S5), which gave rise to the suspicion of meningocele and meningomyelocele, but after complete local assessment and radiological investigations, it was diagnosed finally as an epidermoid cyst. Keeping in mind, the clinical profile, socioemographic factors, and metabolic profile, the intervention of surgical total resection was planned, and the patient was managed.